A hand exercise mobile app for people with rheumatoid arthritis in Turkey: design, development and usability study - TONGA, EDA; ÖZEN BERKOL, TUĞÇE (SPRINGER HEIDELBERG, 2021)
To design and develop a smartphone application for a structured hand exercise programme for patients with rheumatoid arthritis (RA) in Turkey and to test its usability. We followed a two-stage process: (1) Design and Development and (2) Usability testing. In stage 1, we used a qualitative user-centered design approach. We conducted a focus group (8 therapists and people with RA) to discuss the content, features and design to produce a prototype of the application. In a second focus group session, the participants tested the prototype, provided feedback and further revisions were made. In stage 2, 17 participants with RA used the app for 4 to 6 weeks. The System Usability Scale and the adapted Usability, Satisfaction and Ease to Use Questionnaires were used to measure usability, ease of use. Semi-structured interviews were conducted to explore user experiences with the application with 17 participants. In stage 1, the following themes were identified from the focus groups (a) login techniques (b) self-monitoring (c) exercises, (d) exercise diary, (e) information, (f) behavioral change and encouragement (g) exercise adherence. In stage 2, 3 themes were determined from interviews: (a) learning and accuracy, (b) ease of use, (c) motivation and adherence. USE and SUS scores indicated that users reported a high level of usability, satisfaction and ease of use. A mobile app for hand exercise for people with RA was developed using a mixed-method and iterative design. Participants perceived the mobile app as easy to use with high levels of satisfaction.
Keywords: Mobile applications; Exercise; Hand; Rheumatoid arthritis; MHealth; Qualitative research